Miskonsepsi Pemahaman Materi Bangun Datar dengan Penerapan Teori Polya di PGMI 3 - Agilia Febriani; Rora Rizki Wandini (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
This research aims to 1) analyze students' problem solving abilities in solving story problems based on polya stages in plane material in the PGMI 3 class at UIN North Sumatra, 2) find out how to improve students' problem solving abilities in solving story problems based on polya stages. This research uses a qualitative descriptive research type. Data collection in this research was carried out by means of written tests, interviews and documentation. Subjects were taken in this research using purposive sampling technique. Interviews were conducted with research subjects and class teachers. The research results obtained were that students with low abilities were quite capable of goingthrough the stages of understanding the problem and preparing a solution plan. Students with moderate abilities are able to go through the stages of understanding the problem, preparing a solution plan, and implementing the solution plan. Meanwhile, students with high abilities are able to go through all stages of Polya problem solving.